2011
DOI: 10.1007/s00404-011-2182-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and immunoprofile of 30 cases of Brenner ovarian tumors

Abstract: The mean age of the patients was 51.4 years ranging from 16 to 82 years. The tumor was unilateral in 28 cases (16/28 in the right ovary and 12/28 in the left ovary) and bilateral in two cases. Twenty-eight cases (93%) were benign and two (7%) were proliferating (borderline) tumors. Seventeen cases (56%) were pure Brenner tumors, measuring from 0.5 to 2.5 cm and 13 cases (44%) were mixed tumors consisting of a Brenner tumor element and a mucinous ovarian tumor (10/13 cases, 53.8%) and a germ cell tumor in 3/13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 10 publications
(19 reference statements)
0
13
1
Order By: Relevance
“…Seidman and Khedmati [5] reported a similar percentage of Brenner tumors associated with mucinous component. Other smaller studies, including ours, reported a larger percentage of Brenner tumors with mucinous tumor reaching up to 30% [8,12]. This data, however, do not include Brenner tumors with small cysts and or gland-like structures, in part lined by mucinous epithelium that, in our study, accounted for an additional 20% of cases.…”
Section: Discussioncontrasting
confidence: 78%
“…Seidman and Khedmati [5] reported a similar percentage of Brenner tumors associated with mucinous component. Other smaller studies, including ours, reported a larger percentage of Brenner tumors with mucinous tumor reaching up to 30% [8,12]. This data, however, do not include Brenner tumors with small cysts and or gland-like structures, in part lined by mucinous epithelium that, in our study, accounted for an additional 20% of cases.…”
Section: Discussioncontrasting
confidence: 78%
“…In the present case, massive pleural effusion might be due to both pseudo-Meigs' syndrome and metastasis from the borderline mucinous cystadenocarcinoma derived from proliferative BT through metaplasia. Immunohistochemical profiles of the borderline mucinous cystadenocarcinoma and proliferative BT were same (positive for CK 7 and negative for CK 20) [11]. In addition, cytological findings of the pleural effusion were similar to those of the imprint cytology for the tumor.…”
Section: Discussionmentioning
confidence: 51%
“…Brenner tumors (BT) are rare and account for approximately 1%‐2% of all ovarian tumors. While the vast majority of BTs are benign, around 2%‐5% are borderline and malignant variants .…”
Section: Introductionmentioning
confidence: 99%